Pendalilan berasaskan Ayat Al-Ahkam dalam penghujahan hukum Islam semasa: kajian perbandingan di antara fatwa Malaysia dan Brunei Darussalam / Mahyudin Daud - Mahyudin, Daud (2017)
Argumentation based on Ayat al-Ahkam basically was free choice interpretation from the current text that was in conjunction with current problem that occurs as outlined by the jurist. The details of the interpretation is correlated with the individuality of membership with these interpretation that can be considered as complex and capable to process in vowing the togetherness of the sentence from Al-Ahkam by referring the problem that occurred. Fatwa was a basic generic and ground core foundation in interpretation of Al-Ahkam texts that referred according to the jurist kaifiat where it takes as an important role in debating certain events of problem. As it is in Malaysia, fatwa can be define as a result from committing the punishment that is gathered as one voice and being agreed by the Members of National Fatwa Counsel, where all the manner was founded as to inform the law and ethics without being debate by something that can consider important and detail which include the juristic fiction in certain fatwa. There‟s a differences regarding the Fatwa from Brunei that consider as bold and clearer and more to be open to the public by expressing the certain events of problem and was provided by suitable jurisdictions and the testimonial was being declared by a small group of organization that have the authority in forming those events or action. In contexts of interpretation by using the Al-Ahkam text, there‟s a issues by comparing both Malaysia and Brunei, which is the huge gap between both of it. As refer to Malaysia first, when providing or stating the text from Al-Ahkam, there a similarities and differences when it comes to appeal the jurisdiction, when it comes to propose the method or sequence on how it supposed to be done. The purpose of a comparative study done is to take a closer look occurs as outlined adopted by both institutions in the verses of Ayat al-Ahkam as an argument to the establishment of Islamic law for the current problem. This research is combined with both library and field research. The method in collecting the data that used by library research documentation, historical events and interviewed with some of the top scholars from Brunei and Malaysia that involved in collecting and producing the fatwa. In analyzing the data, the deductive, inductive and comparative was being used to gain the result of the research which should be more accurate. The research outcome has shown that, even there was a difference from both fatwa, Malaysia and Brunei that should be more specified on justification of using the Al-Ahkam text, but it still in a form of technical. The basic to the discussion of certain problem or events was based by the jurisdiction was still the same dealing and it contradict from the sequence jurisdiction based from it context as it was providing guideline that was written by scholars. There should be an action taken by JAKIM for the jurist in Malaysia which contain the specific somehow it is valuable in contributing the agreeable among the Muslims in this region. A feedback research should be taken by Brunei Mufti Department in order to observing the acceptance and comprehension among the muslims about the jurisdiction that was implemented in that country. This research also proven that the method of the interpretation from the Al-Ahkam text that used by many scholars, and it is flexible to use in any kind of problem that occurred in certain time.